Pelestarian Nilai-Nilai Budaya Minangkabau Melalui Kegiatan Ekstrakurikuler Sekolah Menengah Pertama - Syahriani, Syahriani; Dirsa, Andika (UIN Imam Bonjol Padang, 2023)
This research was motivated by the cause of juvenile delinquency in SMP Negeri 24 Padang is that not a few junior high school students in adolescence experience deviation by being disrespectful to teachers, saying, rude, not collecting assignments, and skipping classes and climbing fences some students, especially men, are caught smoking in the school environment. Therefore, it is proven as a form of concern for the development of the younger generation, and the increasingly shifting culture in people's lives. Sekolah Menengah Junior (SMP) Negeri 24 Padang is building a